The susceptibility of Islamic banks’ credit risk towards macroeconomic variables - Nursechafia, Nursechafia; Abduh, Muhamad (IIUM Institute of Islamic Banking and Finance, 2014)
Credit risk is the most anticipated risk in the banking system. It is one of the key elements to assess systemic risk and stress testing financial fragility which is very helpful to come up with macro-prudential surveillance in financial systems. Unlike the conventional banking system, there is dearth of empirical study on macro-credit risk in relation with Islamic banking. As such, further research regarding the stability of the Islamic banking industry has become imperative. Accordingly, this paper is aimed at determining and assessing the long run vulnerabilities of Islamic financing sustainability in term of its response to changes in key macroeconomic variables by using time series econometric approaches of cointegration and vector autoregression (VAR). Based on the result of simulating variance decomposition (VD) and impulse response function (IRF), it is found that, sufficient evidence of long-run relationship between credit risk ratio in Islamic banking industry and the selected macroeconomic variables exist. The exchange rate, supply side-inflation, and growth have been indicated to negatively influence credit risk rate in Islamic banking, while money supply and Islamic interbank money market rate positively affect the risk rate.